The non-unicity of the film thickness in the hydrodynamic lubrication: novel approach generating equivalent micro-grooves and roughness - El Gadari, Mhammed; Hajjam, Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
Since the 1960s, all studies have assumed that a film thickness "h" provides a unique pressure field "p" by resolving the Reynolds equation. However, it is relevant to investigate the film thickness unicity under a given hydrodynamic pressure within the inverse theory.
Keywords: Reynolds equation; inverse theory; macro-shape; micro-texture; cavitation; lifting force; friction forces; flow rate